Quantitative SARS-CoV-2 subgenomic RNA as a surrogate marker for viral infectivity: Comparison between culture isolation and direct sgRNA quantification - Scutari, Rossana; Renica, Silvia; Cento, Valeria; Nava, Alice; Sammartino, Josè Camilla; Ferrari, Alessandro; Pani, Arianna; Merli, Marco; Fanti, Diana; Vismara, Chiara; Scaglione, Francesco; Puoti, Massimo; et al. (PloS one, 2023)
Detection of subgenomic (sg) SARS-CoV-2 RNAs are frequently used as a correlate of viral infectiousness, but few data about correlation between sg load and viable virus are available. Here, we defined concordance between culture isolation and E and N sgRNA quantification by ddPCR assays in 51 nasopharyngeal swabs collected from SARS-CoV-2 positive hospitalized patients. Among the 51 samples, 14 were SARS-CoV-2 culture-positive and 37 were negative. According to culture results, the sensitivity and specificity of E and N sgRNA assays were 100% and 100%, and 84% and 86%, respectively. ROC analysis showed that the best E and N cut-offs to predict positive culture isolation were 32 and 161 copies/mL respectively, with an AUC (95% CI) of 0.96 (0.91–1.00) and 0.96 (0.92–1.00), and a diagnostic accuracy of 88% and 92%, respectively. Even if no significant correlations were observed between sgRNA amount and clinical presentation, a higher number of moderate/severe cases and lower number of days from symptoms onset characterized patients with sgRNA equal to or higher than sgRNA cut-offs. Overall, this study suggests that SARS-CoV-2 sgRNA quantification could be helpful to estimate the replicative activity of SARS-CoV-2 and can represent a valid surrogate marker to efficiently recognize patients with active infection. The inclusion of this assay in available SARS-CoV-2 diagnostics procedure might help in optimizing fragile patients monitoring and management.